PENGARUH GAYA KOMUNIKASI ORANG TUA TERHADAP SIBLING RIVALRY ANAK USIA 5-6 TAHUN DI RAUDATUL ATHFAL AL HIDAYAH SEBERANG TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Nopriliani, Dila; Novianti, Ria; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: From the results of the interviews with the parents of children who send her son in Raudatul Athfal al Hidayah Opposite Tembilahan about sibling rivalry known there are 64 children in kindergarten A, there is a half or 38 children who have siblings in the the House. Formulation of the problem in this research are: Whether there is influence of the communication style of parents against the sibling rivalry between the ages of 5-6 years in Raudatul al Hayah Athfal Opposite Tembilahan Indragiri Hilir Regency? The population in this research is elderly Raudatul Athfal al Hidayah Indragiri Hilir Regency Tembilahan Opposite. As for the number of parents is 142 parents who have children attending Raudatul Athfal al Hidayah. Then the sample in this research is as many as 85 people. Based on the research results and discussion, conclusions can be taken there is the influence of parents ' communication styles against Sibling Rivalry between the ages of 5-6 years in Raudatul al Hayah Athfal Opposite Tembilahan Indragiri Hilir Regency. The great influence of the style of communication of the elderly against a Sibling Rivalry between the ages of 5-6 years in Raudatul al Hayah Athfal Opposite Tembilahan Indragiri Hilir Regency of 62.3%.Key Words: Communication Style, Sibling Rivalry